Perancangan Aplikasi Inventory Barang Berbasis Web Pada UMKM XYZ - Dwicahya Supriatman, Rian; Rohayati, Tuti; Sidiq, Maulana (Jurnal Sistem Informasi Galuh, 2025)
In today's digital era, technology has become a primary need in various activities and jobs. The use of the right application can produce the information needed effectively and efficiently, in this ever-evolving era, MSMEs must be able to adapt quickly to technological changes and changing consumer needs. In facing this challenge, efficient stock management is essential for the survival of MSMEs. Well-managed stock is not just a collection of goods stored in a warehouse, but a strategic element in the MSME supply chain. With the existence of a Web-based application, it is hoped that MSMEs in stock management can be better able to avoid excess and lack of stock. MSMEs are also able to respond quickly to changes in demand and internal needs. The design of this application will be made with the PHP, HTML programming languages, and using mySql as its database. The method used in making this application uses the prototyping method. The results of this study are in the form of a web system design that can help MSME owners in managing the Warehouse. The Prototype method is an approach to software development that focuses on creating fast and gradual designs, allowing immediate evaluation of the advantages and disadvantages of prototypes made by prospective users or clients. Developers and clients can engage in continuous interaction during the prototyping process.